Temperature-dependent built-in potential in organic semiconductor devices - Kemerink, Martijn; Kramer, J. M.; Gommans, Hendrikus Hubertus Petrus; Janssen, René A. J. (Applied physics letters, 2006)
The temperature dependence of the built-in voltage of organic semiconductor devices is studied. The results are interpreted using a simple analytical model for the band bending at the electrodes. It is based on the notion that, even at zero current, diffusion may cause a significant charge density in the entire device, and hence a temperature dependent band bending. Both magnitude and temperature dependence of the built-in potential of various devices are consistently described by the model, as the effects of a thin LiF layer between cathode and active layer.